Crop and pasture response to climate change - Tubiello, Francesco N; Soussana, Jean-François; Howden, S. Mark (Proceedings of the National Academy of Sciences - PNAS, 2007)
We review recent research of importance to understanding crop and pasture plant species response to climate change. Topics include plant response to elevated CO₂ concentration, interactions with climate change variables and air pollutants, impacts of increased climate variability and frequency of extreme events, the role of weeds and pests, disease and animal health, issues in biodiversity, and vulnerability of soil carbon pools. We critically analyze the links between fundamental knowledge at the plant and plot level and the additional socio-economic variables that determine actual production and trade of food at regional to global scales. We conclude by making recommendations for current and future research needs, with a focus on continued and improved integration of experimental and modeling efforts.